A Native Whole Blood Assay for Blood-Materials Interaction - Dodds, W Jean; DiNovo, Jean M; Bergeron, John A (Thrombosis and Haemostasis, 1981)
A convenient, accurate, and reproducible method was developed and characterized to test the effects of particulate solids and soluble agents on native whole blood. The effects of citrate anticoagulation and of variation in flow and column parameters were characterized by ancillary experiments. The study utilized a relatively homogeneous strain of large rabbits that had received intravenous [C14]-serotonin as a platelet radiolabel. The assay included a 4 min contact time of either the test sample or saline control with freshly drawn arterial blood and was followed by a series of hemostatic measurements, both before and after passage of the blood through a standard 1 g glass bead column. Changes induced by soluble (ADP, ellagic acid, aspirin) and particulate (collagen) agents in the reactivity of this blood to the subsequent challenge of a large area of reactive surface revealed reproducible quantitative effects on platelets and clotting. Generally comparable results were obtained with native whole human blood when the glass bead surface was adjusted (2 g) for the species difference in coagulability and platelet reactivity.
Keywords: Blood; Materials interaction, native whole blood assay